Las nociones de trabajo informal y trabajo precario en el análisis de la calidad del empleo en Colombia (2014)
In this article the concept of informality in Colombia is evaluated as to its accuracy to provide relevant information on job quality; in the light of multidimensional concepts of precarious employment and job security. The results show that the definition and measurement of informal employment taking place in Colombia remain insufficient to reveal the difficulties workers face in terms of precariousness. This paper proposes a conceptual and operational adaptation of precariousness. The results suggest that the main deficits on job security faced by the Colombian work force are in collective participation, protection against occupational hazards, employee benefits and pension provision. This study concludes that informality does not reflect the wide diversity of precarious work in Colombia, as the latter crosses sector and occupational boundaries of the formal-informal, as recently suggested by the academic debate.